2017
DOI: 10.1093/mnras/stx1812
|View full text |Cite
|
Sign up to set email alerts
|

A transient search using combined human and machine classifications

Abstract: Large modern surveys require efficient review of data in order to find transient sources such as supernovae, and to distinguish such sources from artefacts and noise. Much effort has been put into the development of automatic algorithms, but surveys still rely on human review of targets. This paper presents an integrated system for the identification of supernovae in data from Pan-STARRS1, combining classifications from volunteers participating in a citizen science project with those from a convolutional neura… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 46 publications
(26 citation statements)
references
References 36 publications
0
26
0
Order By: Relevance
“…Other astrophysics research has combined crowdsourcing with machine learning models. Wright et al (2017) classified supernovae in PanSTARRS (Kaiser et al 2010) by aggregating crowdsourced classifications with the predictions of expert-trained CNN and show that the combined human/machine ensemble outperforms either alone. However, this approach is not directly feasible for Galaxy Zoo, where scale prevents us from recording crowdsourced classifications for every image.…”
Section: Active Learning Approach For Galaxy Zoomentioning
confidence: 99%
“…Other astrophysics research has combined crowdsourcing with machine learning models. Wright et al (2017) classified supernovae in PanSTARRS (Kaiser et al 2010) by aggregating crowdsourced classifications with the predictions of expert-trained CNN and show that the combined human/machine ensemble outperforms either alone. However, this approach is not directly feasible for Galaxy Zoo, where scale prevents us from recording crowdsourced classifications for every image.…”
Section: Active Learning Approach For Galaxy Zoomentioning
confidence: 99%
“…Finally, citizen science classifications can be used to train future machine learning algorithms, and the counts produced by each can be cross-validated, ensuring the analyses remain reliable. In fact, Wright et al (2017) demonstrate that a combination of methods (i.e. citizen science and machine learning) can outperform either method used alone 20 .…”
Section: Methodsmentioning
confidence: 96%
“…In fact, Wright et al (2017) demonstrate that a combination of methods (i.e. citizen science and machine learning) can outperform either method used alone 20 .…”
Section: Methodsmentioning
confidence: 96%
“…Ref. 54 found that the human classifications and machine-learning results in Pan-STARRS were complementary; the human classifications provide a pure but incomplete sample while the machine classifications provide a complete but impure sample. By combining the aggregated volunteer classifications with the machine-learning results, they are able to create the most pure and complete sample of new supernovae candidates.…”
Section: Experiments In Machine Integrationmentioning
confidence: 99%